Pengaruh Pelatihan Dan Pengembangan Karir Terhadap Kinerja Karyawan PT Calang Sejati Indah Kota Padang - Aprianda, Rafi; Agussalim, Agussalim; Yanti, Novi (Jurnal Riset dan Sains Ekonomi, 2025)
The aim of the research is to determine the influence of training and career development on the employee performance PT. Calang Sejati Indah kota padang. Data collection methods are field research (Field Research) and library research (Library Research. Types and sources of data are primary data and secondary data. The population of this research is all employees who have attended training at PT. Calang sejati indah kota padang. (Purposive sampling). The data analysis method used is multiple linear regression analysis and determination coefficient. Meanwhile, to test the hypothesis, use the t test and f test. The results of the research are: (1) The most dominant indicator in the employee performance variable is punctuality with an average value of 4.23 and a TCR value of 84.62 in the very good category. The most dominant indicator in the training variable is Training Objectives with an average value of 4.20 and a TCR value of 84.00 in the very good category. The most dominant indicator in the career development variable is information about promotion opportunities with an average value of 4.19 and a TCR value of 83.75 in the very good category. (2) Job training has a significant effect on the performance of PT. Calang Sejati Indah kota padang. (3) Career development has a significant positive effect on the employee performance PT. Calang sejati indah kota padang. (4) Job training and career development have a significant positive effect together on employee performance PT. Calang Sejati indah kota padang. The percentage contribution of the independent variable job training and career development to the dependent variable employee performance is 88.0%. Meanwhile, the remaining 12.0% is influenced by other variables outside this research.